INFRASTRUCTURE DEVELOPMENT IMPLEMENTATION STRATEGY FOR SLUM MANAGEMENT - Mohammad Hasyir; Suryawan Murtiadi; Akmaluddin Akmaluddin (International Journal of Social Science, 2022)
Based on the 2020 West Lombok Regent's Decree, Gerung District, West Lombok Regency, is not included in the list of slum housing and slum settlement locations in West Lombok Regency for 2020 - 2025. The Gerung District area, West Lombok Regency, is facing several settlement problems. Various problems in the Gerung District area such as building conditions, road conditions, drinking water supply conditions, environmental drainage conditions, waste management conditions, and solid waste management conditions. In addition to physical problems, non-physical problems such as social problems and community economic problems are not that high. The purpose of this research is to get the best concept and program to address this area so that it becomes a slum-free settlement in 2023. This research applies the concept of how best to handle this area so that it becomes a slum-free settlement. The implementation strategy is divided into short-term (2023-2024), medium-term (2024-2029) and long-term (2030-2040) programs. The research method used is quantitative and qualitative research methods. Primary data collection is carried out by direct observation to field locations to obtain information and field problems. Interviews were conducted by selecting respondents based on their position. The types of questions are determined based on the needs of the analysis. The secondary data needed is existing settlement data, BPS statistical data on the condition of the local population, and the RTRW map of West Lombok Regency. Slum settlement standards are set based on the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia Number 14/PRT/M/2018. The strategy for managing slum settlements is carried out using the AHP (Analytical Hierarchy Process) method whose goal is to get waste management conditions that have the highest score causing slums and the SWOT analysis methodology to get alternative strategic decisions. This research can be used as material for consideration and input for the West Lombok Regency Government and stakeholders. These results are needed to establish or formulate policies related to infrastructure development to improve the quality of slum settlements, so that the slum-free Gerung District is realized in 2023 and continues. Relevant agencies are expected to make SOPs, carry out periodic monitoring, add competent human resources, activate the website as a media for socialization and outreach as well as a more approach to the community, good coordination with related agencies and other parties in West Lombok Regency as well need to be implemented